ONLINE MEDIA AND ESTABLISHMENT OF STUDENTS' RELIGIOUS UNDERSTANDING IN MADRASAH ALIYAH KENDARI CITY - Paisal Paisal (Al-Qalam, 2021)
This study used a qualitative descriptive method with research problems: How do Madrasah Aliyah students practice religious discourse from online media in their daily lives?, and how do teachers respond and align the religious understanding of Madrasah Aliyah students who interact with the religious discourse from online media?. The research location was in Kendari City, Southeast Sulawesi. The informants were 25 students at MAN 1 Kendari and MAS Ummushabri. The research results found that Madrasah Aliyah students are quite active in accessing religious preaching content using online social media platforms. The online media that is most accessed and used for religious content are Instagram and YouTube in the form of audio-visual videos. The rest are interested in reading status and articles considered to be in line with their understanding. Some of the students follow several popular preachers who are actively spreading religious content on social media. Influenced by online media, some students questioned and challenged the basis of the country, religious traditions, and local traditions addressed to their teachers, families, and relatives. In daily behavior, there is a positive side. Students are more diligent in worshiping and assembling in the Mosque. Madrasah and teachers have issued several protective policies to protect students from easily exposed to radical ideology. The responses and policies include limiting the use of cellphones in schools, intensive religious guidance provided by the teacher, protecting outside groups from entering and providing religious guidance to students, and enrich learning material with religious moderation content on a limited scale.